1997
DOI: 10.1128/mcb.17.10.5843
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of Histone H1-Mediated Transcriptional Repression and Chromatin Compaction by the Acidic Activation Region in Chromosomal Protein HMG-14

Abstract: Histone H1 promotes the generation of a condensed, transcriptionally inactive, higher-order chromatin structure. Consequently, histone H1 activity must be antagonized in order to convert chromatin to a transcriptionally competent, more extended structure. Using simian virus 40 minichromosomes as a model system, we now demonstrate that the nonhistone chromosomal protein HMG-14, which is known to preferentially associate with active chromatin, completely alleviates histone H1-mediated inhibition of transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
114
1
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(121 citation statements)
references
References 74 publications
(111 reference statements)
3
114
1
2
Order By: Relevance
“…6). These results are in line with the observations that HMGNs decrease the compaction of chromatin induced by linker histone H1 in vitro (8) and compete with histone H1 for binding to chromatin in vivo (29). Moreover, our results provide the structural basis for the release of HMGNs from chromatin upon phosphorylation of Ser24 and Ser28 during mitosis (30).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…6). These results are in line with the observations that HMGNs decrease the compaction of chromatin induced by linker histone H1 in vitro (8) and compete with histone H1 for binding to chromatin in vivo (29). Moreover, our results provide the structural basis for the release of HMGNs from chromatin upon phosphorylation of Ser24 and Ser28 during mitosis (30).…”
Section: Discussionsupporting
confidence: 91%
“…High mobility group nucleosomal (HMGN) proteins are a family of such proteins that exist in vertebrate. HMGNs decompact chromatin condensed by the linker histone H1 (8), thereby enhancing transcription activity of the chromatin template. In addition, HMGNs affect DNA repair (9), chromatin remodeling (10), and the extent of histone modifications (11).…”
mentioning
confidence: 99%
“…This intrinsic nucleosomal barrier appears to be modulated to some extent by HMGN1, an architectural chromatin protein that binds to nucleosomes and decompacts chromatin (29,60,61). Although Lim et al (44) reported that HMGN1 diminishes the MSK1-mediated phosphorylation of histone H3 within a nucleosome core particle, our assays show that HMGN1 enhances the MSK1-mediated histone H3 phosphorylation in an activator-dependent manner on a reconstituted nucleosome array, a more physiological context in which HMGN1 interacts with nucleosomes in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…HMGN1 consists of multiple domains, including the nucleosomal binding domain and chromatin unfolding domain (60,61). Because the chromatin unfolding domain is located near, and probably interacts with, the residues 20 -50 of histone H3 (62), this domain may directly shift the position of the histone H3 tail in a manner that would facilitate H3-S10 phosphorylation by MSK1.…”
Section: Discussionmentioning
confidence: 99%
“…As a matter of fact, upstream binding factor 3, a high-mobility-grouplike protein, displaces and causes complete dissociation of histone H1 from rRNA gene enhancers associated with nucleosomes (18). Ding et al have demonstrated that histone H1 can be a functional target of high-mobility-group protein 14 in both transcriptional enhancement and chromatin decompaction (10). Hepatocyte nuclear factor 3 has a configuration very similar to that of histone H1 and, like histone H1, has nucleosome positioning properties (28).…”
Section: Discussionmentioning
confidence: 99%